[Mr. Kent, centre, climbing over the Government front bench with his way blocked by Government Members] - Pryor, Geoff, 1944- (1984)
Your cartoonist was on hand in Parliament during Question Time to record an incident where, during a noisy debate on immigration, an emotional Mr Lewis Kent, Member for the Labor seat of Hotham and himself a Yugoslav-born immigrant, attempted to climb over the furniture to take issue with the Opposition. --Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 9 May 1984.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Politicians -- Australia -- Caricatures and cartoons; Australia -- Politics and government -- 1976-1990 -- Caricatures and cartoons; Federal politicians